The aggregation of Aspergillus spores and the impact on their inactivation by chlorine-based disinfectants. (1st October 2021) - Zhang, Huan; Xu, Xiangqian; Tan, Lili; Liang, Zhiting; Cao, Ruihua; Wan, Qiqi; Xu, Huining; Wang, Jingyi; Huang, Tinglin; Wen, Gang
Highlights: Fungal spores are easy to be aggregated at neutral or alkaline condition. Fungal spores are more resistant to disinfections after aggregation. The percentage of membrane damage of aggregated spores increased more slowly during disinfection. The intracellular ROS level of aggregated spores was lower during disinfection. The increased resistance is due to the difficulty of the disinfectant to penetrate into the aggregates. Abstract: The formation of fungal biofilm goes through some different states, including monodisperse state, aggregated state, germinated state, hyphal and biofilm. The aggregation of spores is a primary step of fungal biofilm development in aquatic systems. Previous studies on the inactivation of fungi were mostly performed in the monodisperse state of fungal spores and biofilm state, however, the inactivation of aggregated fungal spores is still unclear. In this study, the aggregated characteristics of fungal spores ( Aspergillus fumigatus and Aspergillus flavus ) at different pH values were firstly studied, and the inactivation efficiency of fungal spores at different aggregation degree by chlorine-based disinfectants was also clarified. The results showed that the aggregation degree of Aspergillus fumigatus was the highest at pH 9.0 while it was the lowest at pH 5.0. Aggregation between fungal spores was mainly mediated by occasional adhesin–adhesin interactions and electrostatic interactions. Compared with monodisperse spores, fungal spores were more resistant to chlorine-based disinfectants with the increase of spore aggregation degree. The inactivation rate constants of Aspergillus fumigatus at 30% and 63% aggregation degree were 1.5- and 4-folds lower than that of monodisperse spores, respectively. The lower proportion of membrane damage and higher intracellular reactive oxygen species level for aggregated spores than monodisperse spores was observed according to the flow cytometric results after chlorine-based disinfectants treatment. The reasons for the lower inactivation efficiency of aggregated spores are as following: the protection of outer layer spores and signals between aggregates lead to the increase of resistance for aggregated spores. This study is meaningful for the control of the fungal spores at different states in water. Graphic abstract: Image, graphical abstract